Cobra effect in Mexico: social expenditure and poverty, 2008-2018 - Loria, Eduardo; Martínez, Eduardo (Estudios de Economía, 2021)
We examine the efficiency of the cash transfers on multidimensional extreme poverty in the states of Mexico for 2008-2018. We estimate econometric models with panel data with OLS and 2SLS and with cross-section data with GMM that shield against endogeneity of the determinants of poverty. We prove that there are perverse incentives that have caused that transfers perpetuate poverty in the less developed states. Homicides and informal employment have perpetuated it. Agricultural labor productivity, economic growth, productive export orientation, and a better Rule of Law reduce it.